Factors Associated with Intention to Be Vaccinated Against Seasonal Influenza in Healthcare Workers: A Cross-Sectional Study Assessing Health Belief Model Constructs in Serbia - Larisa Vujnovic; Biljana Kilibarda; Sofija Jovanovic; Dragana Dimitrijevic; Milunka Milinkovic; Zoran Bukumiric; Verica Jovanovic (Vaccines, 2026)
Introduction: As seasonal influenza vaccination coverage among healthcare workers (HCWs) in Serbia remains suboptimal, we aimed to identify HCW beliefs associated with their intention to receive seasonal influenza vaccine (“vaccination intention”) in the season 2024/2025. Methods: In a cross-sectional survey conducted in 2024, healthcare institutions were selected from a national registry, using multi-stage sampling stratified by geographical region and healthcare level. All consenting HCWs present on the survey day self-completed questionnaires. Five dichotomised Health Belief Model constructs were assessed: perceived susceptibility to influenza, perceived disease severity, perceived vaccination benefits, perceived physical and psychological barriers, and perceived cues for action (recommendation by another HCW, someone close, or a supervisor). The association of vaccination intention (yes/no/undecided) with Health Belief Model constructs, demographic and occupational factors were assessed using multinomial logistic regression. Results: Of 1919 respondents, 30% declared positive vaccination intention, 52.5% no intention, and 17.5% were undecided. Compared with no intention, positive vaccination intention was associated with perceived self-benefit (aOR = 6.22, CI = 3.49–11.08), perceived patient benefit (aOR = 2.26, CI = 1.48–3.45), perceived susceptibility (aOR = 3.26, CI = 2.19–4.86), and perceived vaccine safety (aOR = 2.95, CI = 1.93–4.50). Participants were more likely to be undecided than reject vaccination if they experienced higher perceived susceptibility (aOR = 2.93, CI = 1.89–4.54), perceived influenza as severe (aOR = 2.04, CI = 1.30–3.21), perceived patient benefits (aOR = 1.77, CI = 1.14–2.74), or recalled receiving a recommendation from another HCW (aOR = 2.63, CI = 1.17–5.85). Conclusions: HCWs’ positive vaccination intention was associated with beliefs relevant for personal health and patient benefits. The undecided group showed a distinct pattern of beliefs warranting their separate analysis and specific approaches.